Model Penerimaan Teknologi dan Kepercayaan Konsumen terhadap Minat Beli Tanaman Hias Melalui E-Commerce Saat Pandemi Covid-19 - Ciryl Sarastila; Vi'in Ayu Pertiwi; Asihing Kustanti (Hasanuddin University, 2021)
The COVID-19 pandemic has caused a change in shopping patterns from offline to online due to the rules to stay at home to reduce the spread of the virus. This pandemic also causes people to look for activities to fill free time at home. One of the rising trends during the pandemic is ornamental plants. This causes ornamental plants to be sold online through e-commerce. Public perception of intention to purchase ornamental plants through e-commerce can be influenced by several factors. This research was aimed to: (1) analyze consumer’s intention to purchase ornamental plants through e-commerce during the COVID-19 pandemic. (2) analyze the effect of Technology Acceptance Model, trust, and perceived risk on intention to purchase ornamental plants through e-commerce. This research is conducted from April to May 2021 in West Java using convenience sampling with a total of 100 respondents. The data analysis technique is carried out using two ways, which are descriptive and inferential statistical with SEM-PLS. The result showed that the intention to purchase ornamental plants through e-commerce during the COVID-19 pandemic is high. Perceived usefulness has a positive and highly significant effect on purchase intention, perceived ease of use has a positive and significant effect on purchase intention, trust has a positive but insignificant effect on purchase intention because it has p-value > 0,1, and perceived risk has a positive and weakly significant effect on purchase intention. Perceived usefulness has the biggest with a coefficient value of 0,553.